2011
DOI: 10.1007/s11056-011-9293-5
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Pinus spp. in South Africa for tolerance to infection by the pitch canker fungus

Abstract: The increasing threats from pests and diseases demand that the South African forest industry explores options to deploy alternative pine species in plantation development. This is especially true for species, such as Pinus patula Schiede and Deppe ex Schltdl. and Cham., which are highly susceptible to the pitch canker fungus Fusarium circinatum. Losses due to F. circinatum have been confined mostly to nurseries and at field establishment resulting in a significant cost to the industry. Although, the fungus has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Bearing in mind that the F. circinatum isolate was the same in both studies, this discrepancy could be due to a genetic effect, since Spanish provenances differ genetically from northern and eastern European provenances [52,53]. The effect of genetic variability on the susceptibility to F. circinatum has been previously demonstrated in other pine species [54][55][56][57][58][59]. This finding highlights the importance of testing the susceptibility not only at species level, but also at provenance level across Europe.…”
Section: Discussionmentioning
confidence: 76%
“…Bearing in mind that the F. circinatum isolate was the same in both studies, this discrepancy could be due to a genetic effect, since Spanish provenances differ genetically from northern and eastern European provenances [52,53]. The effect of genetic variability on the susceptibility to F. circinatum has been previously demonstrated in other pine species [54][55][56][57][58][59]. This finding highlights the importance of testing the susceptibility not only at species level, but also at provenance level across Europe.…”
Section: Discussionmentioning
confidence: 76%
“…Variation in susceptibility to F. circinatum has been found using stem inoculation screening trials at the between species level (Hodge & Dvorak 2000, Mitchell et al 2012b, provenance and family level within species (Hodge & Dvorak 2007, Mitchell et al 2012c and for hybrid combinations of P. patula with species more tolerant of F. circinatum (Roux et al 2007, Mitchell et al 2013. Use of genetically tolerant planting stock and nursery hygiene measures are both important elements of an integrated pest management strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, taking into account that intraspecific genotypic variation has been recognized as a source of resistance to F. circinatum in other pine species [33,35,45,[64][65][66], the genetic effect should not be dismissed. In fact, Martín-García et al [50] found that Romanian provenance of P. sylvestris was not susceptible to F. circinatum and this resistance was related to the high genetic variability of European Scots pine populations [67,68].…”
Section: Discussionmentioning
confidence: 99%